The Web-Based Advance Care Planning Program "Explore Your Preferences for Treatment and Care": Development, Pilot Study, and Before-and-After Evaluation - Doris van der Smissen; Judith A C Rietjens; Sandra van Dulmen; Ton Drenthen; F Ragnhild M D Vrijaldenhoven-Haitsma; Marijke Wulp; Agnes van der Heide; Ida J Korfage (JMIR Publications, 2022)
BackgroundWeb-based advance care planning (ACP) programs may support patients in thinking about and discussing their preferences for future treatment and care. However, they are not widely available, and only a limited number of programs are evidence based. ObjectiveWe aimed to develop and evaluate an evidence-based, interactive web-based ACP program that guides users through the process of thinking about, discussing, and recording of preferences for treatment and care. MethodsThe program "Explore your preferences for treatment and care" was developed, pilot-tested on feasibility, and subsequently evaluated; engagement in ACP was assessed before program completion and 2 months after program completion using the ACP Engagement Survey (score 1-5) among 147 persons with chronic disease. Usability (score 0-100) and user satisfaction (score 1-5) were also assessed. ResultsACP engagement increased from 2.8 before program completion to 3.0 two months after program completion (P<.001); contemplation about ACP increased from 2.6 to 2.8 (P=.003), and readiness for ACP increased from 2.2 to 2.5 (P<.001). No changes were found for knowledge about ACP (3.0-3.2; P=.07) and self-efficacy for ACP (3.8-3.8; P=.25). The program was perceived as usable (mean 70, SD 13), attractive (mean 3.8, SD 0.7), and comprehensible (mean 4.2, SD 0.6). ConclusionsWe developed an evidence-based, interactive web-based ACP program in cocreation with patients, relatives, and health care professionals. Before-and-after evaluation showed that the program can support people in taking first steps in ACP and in reflecting on preferences for treatment and care, by guiding them through the process of ACP using a stepwise approach. Participants perceived the program as usable and understandable, and they were satisfied with the program and with the amount of information. Health care professionals may use the program as a tool to start ACP discussions with their patients. The program may increase awareness of ACP.